A Study on the Effects of Dry Needling in Multiple Sclerosis Patients with Spasticity: Protocol of a Randomized Waitlist-Controlled Trial - Omid Motamedzadeh; Noureddin Nakhostin Ansari; Soofia Naghdi; Amirreza Azimi; Ashraf Mahmoudzadeh; Sandra Calvo; Pablo Herrero (Medical Association of Pharmacopuncture Institute, 2021)
Background : Spasticity is a common symptom in multiple sclerosis (MS). Dry needling (DN) has been considered a useful method for the treatment of spasticity; however, there are no studies on the effects of DN on spasticity in patients with MS. We propose a study protocol aiming to investigate the effects of DN on spasticity in patients with MS. Methods : MS patients with plantar flexor spasticity will be recruited. Participants will be randomly assigned to the DN group, where they will be receiving a single session of DN, one minute for each head of gastrocnemius muscle, or to the waiting list control group with no intervention. Primary outcome measures are the Modified Ashworth Scale (MAS) for gastrocnemius spasticity, passive resistive torque, and podography for foot pressure distribution. The ankle active and passive range of dorsiflexion and Timed Up and Go tests are the secondary outcome measures. All outcomes will be measured at baseline, immediately after the intervention, and one week later. A mixed-model, general linear model, and two-way repeated-measures ANOVA will be used to compare the quantitative variables between groups and within groups at the measurement time points. The MAS ordinal measure of spasticity will be compared between groups using the Kruskal-Wallis test, and both the Friedman test and Wilcoxon test will be used for within-group changes. Discussion: This study will provide primary evidence on the effects of DN on gastrocnemius muscle spasticity and gait in patients with MS. Trial registration: Iranian Registry of Clinical Trials (IRCT): IRCT20190617043918N1.